Harlequin Bioethics, Servant of Two Masters / Bioéthique Harlequine, servante de deux maîtres - Bélisle-Pipon, Jean-Christophe (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Bioethics, like the sixteenth-century commedia dell’arte, is a master of revelation. At the heart of this is a propensity to highlight that what we see is as much truthful and elegant as it is made up of pretence and staging. Must we persuade ourselves that what is false is not false, that what is true is changeable and fragile? Is it possible to serve two masters? Is it possible to get by without antics and disgrace? The Odelet is at once a cryptic portent of the past, present and future of bioethics and a reflection on the capacity of the field (and its actors) to act as a motor for social change.